Basic and Potential Sectors Driving Economic Growth in Bulungan Regency - Cancy Alexiana; Kurniawan Kurniawan; Karolus Sonu (Diponegoro Journal of Economics, 2025)
Bulungan Regency, as the capital of North Kalimantan Province, can become a new growth center in the province. This study aims to identify the basic economic sectors and potential drivers of economic growth in Bulungan Regency. This study uses data from the Central Statistics Agency (BPS) of Bulungan Regency and North Kalimantan Province for 2023-2025. The data analysis technique used was the Location Quotient (LQ) to identify basic sectors and the Klassen Typology to identify potential sectors in Bulungan Regency. The data analysis shows that the basic sectors in Bulungan Regency are agriculture, forestry, and fisheries; industrial management, construction; water supply; waste management, waste and recycling; information and communication; real estate; government administration; defense; and mandatory social security; education; and other services. The data analysis also indicates that potential sectors in Bulungan Regency are construction and financial and insurance services. The Bulungan Regency government can provide significant support to these potential sectors by providing easier financial access. Investors have the opportunity to invest in several potential sectors. Investors can also invest in sectors that have developed and grown rapidly in Bulungan Regency. The contribution of this research lies in providing a comprehensive understanding of the basic and potential sectors that can drive economic growth in Bulungan Regency.